STRUKTUR SOSIAL DAN KEPRIBADIAN PESERTA DIDIK DI LEMBAGA PENDIDIKAN DAN MASYARAKAT - Krisno, Krisno; Ridho, M; Ubabuddin, Ubabuddin (ILJ: Islamic Learning Journal, 2024)
this article discusses the social structure and personality of learners  in educational institutions and society. This research is a library research with content analysis method. The results of the study state Social structure is the behavior between humans, humans and other community groups. Humans are social creatures who need each other. Humans cannot be separated from social interactions between communities and need help from birth to death. Humans cannot develop with the help of others.  In society, humans interact with each other, in society there are different social structures and social structures are not related to the personality of the community itself.